2020
DOI: 10.22541/au.159188592.22056384
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early and late postpartum depression exhibit distinct correlates: the IGEDEPP prospective cohort study

Abstract: Objective To identify risk factors of early and late postpartum depression (PPD) among a wide range of variables including sociodemographic characteristics, childhood trauma, stressful life events during pregnancy, and history of personal and family psychiatric disorders; and to assess the contribution of each risk factor. Design Nested case-control in a prospective longitudinal cohort study. Setting Eight maternity departments in Paris metropolitan area, France. Sample 3310 women with deliveries between Novem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In case of MDE history, the perinatal context was assessed by a question: "Did this episode occur during or following a previous pregnancy?" PPD corresponded to having experienced a PPD between birth and 1 year postpartum: we pooled women with early-onset PPD, assessed during the second interview (at 8 weeks postpartum), and those with late-onset PPD, assessed during the third one (at 1 year postpartum), using DSM-5 diagnostic criteria of MDE [29,30].…”
Section: Assessmentsmentioning
confidence: 99%
“…In case of MDE history, the perinatal context was assessed by a question: "Did this episode occur during or following a previous pregnancy?" PPD corresponded to having experienced a PPD between birth and 1 year postpartum: we pooled women with early-onset PPD, assessed during the second interview (at 8 weeks postpartum), and those with late-onset PPD, assessed during the third one (at 1 year postpartum), using DSM-5 diagnostic criteria of MDE [29,30].…”
Section: Assessmentsmentioning
confidence: 99%
“…This disorder is a complex multifactorial disease with sociodemographic, environmental, psychiatric, and genetic determinants [ 1 , 14 , 15 ]. We have previously shown that sociodemographic, clinical, and environmental determinants of early- and late-onset PPD are different, suggesting partially overlapping pathophysiological mechanisms [ 15 , 16 ]. However, in both types of PPD, personal and family histories of depression are important risk factors for PPD, suggesting a genetic vulnerability.…”
Section: Introductionmentioning
confidence: 99%